(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the deepening of economic globalization and the domestic reform and opening up process, coupled with the continuous acceleration of industrialization and urbanization, a series of problems related to national security, such as ecological and environmental protection pressure, shortage of cultivated land resources and shortage of food supply, have been highlighted, and the foreign investment of China’s agricultural enterprises is needed.By analyzing the micro data, we find that state-owned agricultural enterprises prefer developing countries, while private enterprises prefer developed countries, which put forward the problems existing in the current process of foreign direct investment of agricultural enterprises and put forward relevant suggestions.